The socio-cultural aspects of sexual medicine: recommendations from the Fifth International Consultation on Sexual Medicine - Osur, Joachim et. al... (Oxford University Press, 2025)
Introduction: The intersection of culture, history, religion, traditions, laws, political trends, and evolving attitudes affects sexual expression and acceptance or rejection of sexual practices. Clinicians and clinical care are affected by these factors as well, although clinicians are not always aware of the way in which their training, their own experiences and attitudes influence the way in which they approach patients. In this paper, we contextualize a nd then describe 2 areas of sexual practices and 1 area of sexual difficulty that sexual medicine clinicians encounter in their practice, namely, the practice of female genital mutilation/cutting, penile circumcision, and the experience of unconsummated marriages. Materials and Methods: Given the emerging knowledge of the socio-cultural aspects of sexual medicine, we conducted a narrative review of the extant literature through wide searches in PubMed, Google, and on global websites relevant to this topic, such as the World Health Organization, the United Nations, and others. The content of this paper was reviewed by all the authors, discussed w here disagreements occurred, or additional perspectives were needed, and further literature was incorporated. Results: We describe known practices of female genital cutting/mutilation and penile circumcision, their perceived benefits, and harms, but also with a view to the importance of patient empowerment and respect for self-determination. We discuss unconsummated marriages as the result of often culturally determined insufficient sex education and guidance, as well as clinical resources. Discussion: We recommend that clinicians approach patients with both curiosity and cultural humility and that the International Society for Sexual Medicine (ISSM) adopt a strong ethical perspective as a part of the ongoing discourse on these practices and experiences.
Keywords: culture; sexuality; female genital mutilation/cutting; penile circumcision; unconsummated marriage; ethics; informed consent.